Stability and Analysis of Vibrations Bifurcation Based on Dynamic Modeling of a Solar Titan 130 Gas Turbine - Alaoui Merouane; Iratni Abdelhamid; Alshammari Obaid S.; Hafaifa Ahmed; Colak Ilhami; Guemana Mouloud (Journal of Mechanical Engineering, 2022)
This work is interested in studying the vibrations’ stability in gas turbines, compared to a dynamic model of the Jeffcott rotor, the parameters of the gas turbine will be estimated for the purpose of developing a mathematical model which points out the behavior of the turbine rotor in virtue of the data of actual vibration measurements. The addition of the geometric nonlinearities of the vibrations unveils a supercritical Hopf bifurcation, the unstable modes are repulsed towards a stable limit cycle of small radius. The vibration measurements and analyzes were performed on a gas turbine Solar TITAN 130 type mounted in a gas compression station in Djelfa, Algeria. The turbine was in the operating mode when the vibration parameters were read. Bifurcation monitoring bounds the specific operating ranges, extracts efficiently the dynamic behavior core of the studied turbine and consequently affords a new approach to efficiently dimension the turbine rotor.